Non-alcoholic Fatty Liver Disease and the Risk of Incident Atrial Fibrillation in Young Adults: A Nationwide Population-Based Cohort Study - Choi, JungMin; Lee, So-Ryoung; Choi, Eue-Keun; Ahn, Hyo-Jeong; Kwon, Soonil; Park, Sang-Hyeon; Lee, HuiJin; Chung, Jaewook; Han, MinJu; Lee, Seung-Woo; Han, Kyung-Do; Oh, Seil; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is a multisystem disease including cardiovascular. However, the association between NAFLD and the risk of incident atrial fibrillation (AF), especially in young adults, remains unclear. We aimed to evaluate the association between NAFLD as assessed by the fatty liver index (FLI) and the risk of AF in young adults. Methods: We identified individuals aged 20–39 years who underwent health examinations conducted by the Korean National Health Insurance Corporation between January 2009 and December 2012. Individuals with significant liver disease, heavy alcohol consumption, or prevalent AF were excluded. We categorized based on FLI: <30, 30–60, and ≥60. Incident AF was evaluated as the primary outcome. Results: We included 5,333,907 subjects (mean age, 31±5 years; men, 57%). During a mean follow-up of 7.4±1.1 years, 12,096 patients had newly diagnosed AF (incidence rate 0.31 per 1000 person-years). After adjustment, subjects with FLI 30–60 and FLI ≥60 showed a higher risk of AF compared to those with FLI <30 (hazard ratio [HR] 1.21, 95% confidence interval [CI, 1.15–1.27] and HR 1.47, 95% CI [1.39–1.55], p<0.001, respectively). In women, the increased AF risk was accentuated in the higher FLI group than in the individuals with FLI<30, compared with men (p-for-interaction = 0.023). A higher incident AF risk in the higher FLI groups was consistently observed in various subgroups. Conclusion: Among young adults, NAFLD assessed using FLI was positively correlated with the AF risk. These findings support the evidence of AF screening in young adults with high FLI scores.